Development of Mobile Based Educational Game as a Learning Media for Basic Programming in VHS - Hakkun Elmunsyah; Gradiyanto Radityo Kusumo; Utomo Pujianto; Didik Dwi Prasetya (IAES Indonesia Section, 2018)
The purpose of this research is to develop mobile based education game which will be used as the learning media of basic programming for grade X VHS student as well as to know the its eligibility level. The developed education game consists of four basic programming competencies. This learning media is developed using ADDIE model with waterfall model for the flow development. The validation process involved 2 material experts, 1 media expert, and two groups of eligibility testing. The type of data is qualitative and quantitative with the method of data collection is questionnaire. The measurement uses five scale of likert. This study concluded that the developed educational game are valid and eligible to be used as a basic programming learning media.